Penyuluhan investasi kesehatan gizi dan pemilihan skincare aman bagi remaja: Upaya preventif kesehatan kulit dan tubuh sejak dini - Rahayu, Ericha Wanda Puji; Pramudya, Iren Dwi Puspita; Wardhani, Erny Kusuma; Putri, Khansa Fidelya Wahyu; Aziiza, Naura Rachma; Mulyawan, Fajar; Mahdavikia, Muhammad Fachryan; Putri, Meilani Rahma; Alisya, Nur; Atmadani, Rizka Novia (Tintamas: Jurnal Pengabdian Indonesia Emas, 2025)
This activity is a counselling session conducted by a group of students from the University of Muhammadiyah Malang at SMA Muhammadiyah 1 Malang. Counseling on Nutritional Health Investment and Selection of Safe Skincare Products for Adolescents. This counselling aims to educate, provide understanding, and increase awareness among high school students as an adolescent age group who are experiencing physical, emotional, and social transitions, that balanced nutrition is important in supporting growth and long-term health and also the importance of choosing skincare products that are appropriate for skin type and age. The implementation of this activity employs an educational counselling approach for students of SMA Muhammadiyah 1 Malang. The procedure for implementing the activity involves the delivery of the first material on nutritional health investment, followed by the next material on choosing safe skincare for adolescents. A questionnaire was also held to determine the level of understanding of SMA Muhammadiyah 1 Malang students regarding the material that has been delivered. The results of the post-test, carried out by approximately 70 students, showed an excellent level of understanding.